2019
DOI: 10.1016/j.afjem.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Mixed methods process evaluation of pilot implementation of the African Federation for Emergency Medicine trauma data project protocol in Ethiopia

Abstract: Introduction The African Federation for Emergency Medicine Trauma Data Project (AFEM-TDP) has created a protocol for trauma data collection in resource-limited settings using a clinical chart with embedded standardized data points that facilitates a systematic approach to injured patients. We performed a process evaluation of the protocol’s implementation at Tikur Anbessa Specialized Hospital in Addis Ababa, Ethiopia to provide insights for adapting the protocol to our setting. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…However significant challenges exist with relying on clinical staff to collect injury data including clinical staff capacity, the quality of data, lack of resources, insufficient prehospital care, and difficulty with administrative duties and hospital organisation [27]. Such challenges can undermine the value of the data collected as evidenced through one recent, well organised study in Ethiopia which found a capture rate of just 21% for injury data on their clinical data tool [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However significant challenges exist with relying on clinical staff to collect injury data including clinical staff capacity, the quality of data, lack of resources, insufficient prehospital care, and difficulty with administrative duties and hospital organisation [27]. Such challenges can undermine the value of the data collected as evidenced through one recent, well organised study in Ethiopia which found a capture rate of just 21% for injury data on their clinical data tool [31].…”
Section: Discussionmentioning
confidence: 99%
“…A standardised data collection form has been developed drawing on a number of existing tools including the African Federation of Emergency Medicine [31], the World Health Organisation [17] and the Home and Leisure Accident and Surveillance System (HASS) from the Royal Society for the Prevention of Accidents [32], developed and adapted for the Nepal context. The data collection form will not replace existing clinical records as the existing clinical record keeping in the two study sites are not sufficiently detailed or reliable to capture the required epidemiological or clinical data on injuries.…”
Section: Data Collection Surveillance Datamentioning
confidence: 99%
“…The injury severity was classified as ‘minor’ (superficial injury such as bruises or cuts), ‘moderate’ (injures requiring skilled treatment), or ‘severe’ (injures requiring intensive management), depending on the level of requirement for skilled emergency care intervention. A standardised data collection form was developed from existing tools [ 13 , 23 , 24 ], adapted for the Nepal context, and piloted prior to data collection. All data collection was conducted in the Nepali language.…”
Section: Methodsmentioning
confidence: 99%
“…Projects do not need to be expensive, reliant on large data sets or implemented across countries, although studies such as FEAST [ 24 ] and CRASH-2 [ 25 ] demonstrate that high quality and impactful quantitative research in LMICs is possible. Important and relevant EC publications using qualitative and mixed methods from Africa [ 26 , 27 ] and the Pacific region [ [28] , [29] , [30] ], for example, also illustrate that meaningful research can be locally-devised, inexpensive and single-site.…”
Section: Research Priorities In Emergency Carementioning
confidence: 99%
“…The examples provided earlier in this paper from the Pacific region, regarding trauma care in Fiji [ 30 ], asthma management in Papua New Guinea [ 28 ] and triage in the Solomon Islands [ 29 ], have all used a qualitative ‘action research’ framework to explore the implementation science, and simple quantitative methods to measure outcomes. In Africa, mixed methods have been to describe and evaluate a training program [ 26 ], and to analyse the introduction of a new process for trauma data collection [ 27 ]. These approaches are highly acceptable and have great utility in resource limited contexts; they provide rich data on the real-life experiences, outcomes and challenges involved with implementing a new intervention to improve clinical care or develop an EC system.…”
Section: Qualitative Approachmentioning
confidence: 99%